ILRI 40 years: Reflections on day 1 by Jimmy Smith - Smith, Jimmy W. (International Livestock Research Institute, 2014)
Reflections by Jimmy Smith (ILRI) on the first day of the ILRI@40 Conference: Livestock-based options for sustainable food and nutritional security, economic well-being and healthy lives, Addis Ababa, Ethiopia, 6–7 November 2014.